Overall Survival and Related Factors of Advanced-stage Epithelial Ovarian Cancer Patients Underwent Debulking Surgery in Jakarta, Indonesia: A Single-center Experience - Winarto, Hariyono; Welladatika, Adithya; Habiburrahman, Muhammad; Purwoto, Gatot; Kusuma, Fitriyadi; Utami, Tofan Widya; Putra, Andi Darma; Anggraeni, Tricia; Nuryanto, Kartiwa Hadi (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The worrisome prognosis of advanced-stage epithelial ovarian cancer (EOC) needs a new perspective from developing countries. Thus, we attempted to study the 5-year overall survival (OS) of advanced-stage EOC patients who underwent debulking surgery in an Indonesian tertiary hospital. METHODS: A retrospective study recruited forty-eight subjects between 2013 and 2015. We conducted multiple logistic regression analyses to predict risk factors leading to unwanted disease outcomes. The OS was evaluated through the Kaplan–Meier curve and Log-rank test. Cox proportional hazards regression examined prognostic factors of patients. RESULTS: Prominent characteristics of our patients were middle age (mean: 51.9 ± 8.9 years), obese, with normal menarche onset, multiparous, not using contraception, premenopausal, with serous EOC, and FIGO stage IIIC. The subjects mainly underwent primary debulking surgery (66.8%), with 47.9% of all individuals acquiring optimal results, 77.1% of patients treated had the residual disease (RD), and 52.1% got adjuvant chemotherapy. The risk factor for serous EOC was menopause (odds ratio [OR] = 4.82). The predictors of suboptimal surgery were serous EOC (OR = 8.25) and FIGO stage IV (OR = 11.13). The different OS and median survival were observed exclusively in RD, making it an independent prognostic factor (hazard ratio = 3.50). 5-year A five year OS and median survival for patients with advanced-stage EOC who underwent debulking surgery was 37.5% and 32 months, respectively. Optimal versus suboptimal debulking surgery yielded OS 43.5% versus 32% and median survival of 39 versus 29 months. Both optimal and suboptimal debulking surgery followed with chemotherapy demonstrated an OS 40% lower than those not administered (46.2% and 20%, respectively). The highest 5-year OS was in serous EOC (50%). Meanwhile, the most extended median survival was with mucinous EOC (45 months). CONCLUSION: Chemotherapy following optimal and suboptimal debulking surgery has the best OS among approaches researched in this study. RD is a significant prognostic factor among advanced-stage EOC. Suboptimal surgery outcomes can be predicted by stage and histological subtype.